An experimental study on the ignition and combustion characteristics of ultrafine Boron particles - He, Ruining; Bai, Xin; Ren, Xuan; Zhao, Yilin; Wang, Xin; Liang, Jinhu; Qin, Fei; Sun, Ce; Yun Hin, Taufiq Yap; Zhou, Chong Wen; Curran, Henry J.; Li, Yang (Elsevier, 2026)
Due to its higher energy density, clean combustion products, and a significant reduction in two-phase flow heat loss, Boron powder is widely used in solid propellants as an additive to enhance combustion reactivity. However, the lack of experimental data on nanoscale boron particle combustion makes its combustion process unclear. In this study, Ignition delay times (IDT) and burn time characteristics for ultrafine boron particles (30 nm) were systematically investigated in 5 different oxidant conditions at 2.0 bar using a shock tube experimental system. For comparison, aluminium particles (50 nm) and magnesium particles (30 μm) selected as control groups and had also been conducted investigation works under the same experimental conditions as boron. IDTs for all three metals were significantly higher in H2O atmospheres compared to other oxidants, and this aligns with the conclusions drawn by Wu [1] , further indicating that as the H2O concentration increases, the combustion mode of the three particles transitions towards a diffusion-controlled regime. For boron particles in multi-component oxidants, adding oxygen consistently increased IDT across the tested temperature range compared to oxygen-free conditions. Meanwhile, by calculating the Knudsen and Fourier numbers, the physical heat-conduction time of boron particles in profile-5 was analysed with molecular collision theory, which only takes 0.1 microseconds, so it could be ignored compared to IDT. SEM and energy spectra analysis characterized boron combustion products under different oxidants. Combustion efficiency (η) for boron was calculated by comparing reactive and oxide contents in samples and products. Results showed that steeper slopes in boron burn time data (indicating lower activation energy) correlated with lower combustion efficiency. The results of the current study provide data for the construction of a detailed combustion chemical kinetic mechanism of the tree metal particles, and the design of metal-containing fuel engines.